PENGEMBANGAN DESTINASI WISATA KLENIK TAMAN NASIONAL ALAS PURWO DI KABUPATEN BANYUWANGI - Lilit Biati; Abdul Aziz; Moh. Imam Khaudli (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2020)
The Klenik Tourism of the Alas Purwo National Park is visited by many groups of people especially shamans who come to the Alas Purwo National Park from various regions and various religious identities. They did not come alone but by bringing their men to Alas Purwo National Park to perform rituals in the caves and Pancur Beach in the Pancur Resort. In the caves they do semedi also bring the necessary equipment such as incense, flowers, and incense. Because the place is indeed in the forest and still sacred, they still come back to Alas Purwo National Park with certain needs including seeking peace, penance, rituals with a specific purpose. obstacles encountered in efforts to develop the occult destinations of the Alas Purwo National Park, Analyze and Explain the factors that support the success in the development of the occult destinations of the Alas Purwo National Park in Banyuwangi Regency. That is why this research was conducted using qualitative research methods and the analysis used an interactive model (Miles and Hubermen), namely by reducing data, presenting data and drawing conclusions. From several research findings, it was concluded that there were factors that triggered them to do heresy including: insufficient economic needs, repentance or calming down to pray, meditation with specific goals, economic adequacy, shifting life in the family. The occult process is basically the same as people doing rituals, meditation or the like in different ways and places according to the stability of the individual with all kinds of equipment that they think are important for example by bringing offerings, flower flowers, flower flowers, telon flowers, incense or incense. According to the study of occult marketing theory conducted by visitors of the Alas Purwo National Park, it can add to the income of the Alas Purwo National Park, this can be proven by looking at visitor data through the increasing entrance of Rowobendo, due to the increasing number of people from various regions visiting the Park The Alas Purwo National Park which was invited by previous visitors who had performed the ritual by directly speaking to the people who had never visited Alas Purwo National Park, so that those who had never been to the Alas Purwo National Park had a curiosity by joining with those who have performed rituals in Alas Purwo National Park with various successes which according to them have changed their lifestyle after visiting Alas Purwo National Park.